2013
DOI: 10.1038/emboj.2013.76
|View full text |Cite
|
Sign up to set email alerts
|

MAP1B regulates microtubule dynamics by sequestering EB1/3 in the cytosol of developing neuronal cells

Abstract: MAP1B, a structural microtubule (MT)-associated protein highly expressed in developing neurons, plays a key role in neurite and axon extension. However, not all molecular mechanisms by which MAP1B controls MT dynamics during these processes have been revealed. Here, we show that MAP1B interacts directly with EB1 and EB3 (EBs), two core 'microtubule plus-end tracking proteins' ( þ TIPs), and sequesters them in the cytosol of developing neuronal cells. MAP1B overexpression reduces EBs binding to plus-ends, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 49 publications
7
86
1
Order By: Relevance
“…4D, Movie S3, clips 1 and 2, respectively, and Table S3); however, the Pk pkexpressing larvae showed a significant increase in the length of the EB1-GFP comets compared to control larvae (Mann-Whitney U, P < 0.0001; Fig. 4E), demonstrating that there is an increase in MT plus-end polymerization when the balance is tipped in favor of the Pk pk isoform (22,23). In neurons expressing the Pk sple isoform, a large fraction of the MTs were actually reversed in orientation, with 36% of the comets moving toward the cell body and 64% of the comets moving toward the nerve terminal (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4D, Movie S3, clips 1 and 2, respectively, and Table S3); however, the Pk pkexpressing larvae showed a significant increase in the length of the EB1-GFP comets compared to control larvae (Mann-Whitney U, P < 0.0001; Fig. 4E), demonstrating that there is an increase in MT plus-end polymerization when the balance is tipped in favor of the Pk pk isoform (22,23). In neurons expressing the Pk sple isoform, a large fraction of the MTs were actually reversed in orientation, with 36% of the comets moving toward the cell body and 64% of the comets moving toward the nerve terminal (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…40 Moreover, expression of EB1/3 and MAP1B is enriched along extending neurites and axons. 10 As shown in the model presented in Figure 1A, we have recently shown that MAP1B interacts directly with EB1/3 and sequesters them in the cytosol of developing neuronal cells thereby regulating MT dynamics in a coordinated fashion. 10 We propose that MAP1B reduces the effective pool of cytosolic EBs available to interact with MT plusends, thus keeping the high MT dynamicity required during axonogenesis.…”
Section: Map1b Sequesters Ebs In the Cytosol Of Extending Neurites/axmentioning
confidence: 99%
“…10 As shown in the model presented in Figure 1A, we have recently shown that MAP1B interacts directly with EB1/3 and sequesters them in the cytosol of developing neuronal cells thereby regulating MT dynamics in a coordinated fashion. 10 We propose that MAP1B reduces the effective pool of cytosolic EBs available to interact with MT plusends, thus keeping the high MT dynamicity required during axonogenesis. In particular, the MAP1B/EBs crosstalk in growth cones contributes to growth cone remodeling and proper advance during axon outgrowth.…”
Section: Map1b Sequesters Ebs In the Cytosol Of Extending Neurites/axmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them, like tau or MAP2, induce MT bundling, whereas others like MAP4 do not have bundling activity (Burgin et al 1994;Kanai et al 1989Nguyen et al 1997;Olson et al 1995). In addition, MAP1B has been shown to control MT dynamic, while MAP4 alters MT surface properties and affects motor protein activity Samora et al 2011;Semenova et al 2014;Tokuraku et al 2007;Tortosa et al 2013;Utreras et al 2008). Interestingly, many of these MAPs not only bind MTs but also interact with actin and participate in numerous signal pathways.…”
Section: Classical Mapsmentioning
confidence: 99%